Design Intelligent Protection System Based Microcontroller - Qabas Abdal Zahraa Jabbar (Newinera Publisher, 2023)
Protecting vaccines and making sure they are still good until they are used is a problem that hurts people, especially in countries that don't have the right facilities to make sure vaccines are still good. This is because vaccines can lose their effectiveness if they are used in places other than where they were made. Whether you're putting something away or moving it, it's best to hold it back. In this project, we're going to build a system that will keep an eye on the COVID-19 vaccine and let people know if a vaccine isn't available because of a problem in the supply chain. The system has a microcontroller called the Arduino UNO, a temperature sensor, a GSM type SIM900, and a GPS device. The vaccine storage is measured by the temperature sensor. Messages are sent and received using GSM, which stands for